2021
DOI: 10.3389/fphys.2021.787535
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transport in Brown Adipocyte Thermogenesis

Abstract: Non-shivering thermogenesis is an energy demanding process that primarily occurs in brown and beige adipose tissue. Beyond regulating body temperature, these thermogenic adipocytes regulate systemic glucose and lipid homeostasis. Historically, research on thermogenic adipocytes has focused on glycolytic metabolism due to the discovery of active brown adipose tissue in adult humans through glucose uptake imaging. The importance of lipids in non-shivering thermogenesis has more recently been appreciated. Uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 138 publications
0
12
0
Order By: Relevance
“…To gain more insight into these processes, we grew white adipocytes in media supplemented with a single nutrient (fatty acid or glucose) and then evaluated mitochondrial oxygen consumption, since it is well-known that thermogenic adipocytes (brown and beige cells) manage lipid and glucose homeostasis in order to modulate body temperature. Heat production, or thermogenesis, is a powerful energetic mechanism, and brown adipocytes need a fast and accessible power source, represented principally by glucose and/or free fatty acids [ 33 , 34 ]. Our results were consistent with the findings reported in the literature: in the presence of glucose, we observed an increase in mitochondrial oxygen consumption, primarily after treatment with GW, SID, and IRI ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…To gain more insight into these processes, we grew white adipocytes in media supplemented with a single nutrient (fatty acid or glucose) and then evaluated mitochondrial oxygen consumption, since it is well-known that thermogenic adipocytes (brown and beige cells) manage lipid and glucose homeostasis in order to modulate body temperature. Heat production, or thermogenesis, is a powerful energetic mechanism, and brown adipocytes need a fast and accessible power source, represented principally by glucose and/or free fatty acids [ 33 , 34 ]. Our results were consistent with the findings reported in the literature: in the presence of glucose, we observed an increase in mitochondrial oxygen consumption, primarily after treatment with GW, SID, and IRI ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…42,43 The lipolysis of TG to liberate FFAs and glycerol is necessary for WAT browning, and the released FFAs can be oxidized in mitochondria to generate heat. 44 Complete lipolysis requires a series of lipases and is regulated by PKA. 45 In the present study, we found that OKC induces the phosphorylation of PKA and increases the expression of the lipolytic enzymes ATGL, p-HSL, and MGL, which results in less TG storage in WAT.…”
Section: Discussionmentioning
confidence: 99%
“…These thermogenic adipocytes are considered to have unique developmental origins, bioenergetics, and physiological functions. Thermogenic adipocytes use lipid and glucose to regulate body temperature [ 21 , 22 ]. Consistent with previous studies, our results support that H3 Ab induces stem cells to differentiate into brown adipocyte-like cells, and these cells contribute to increased production of heat energy and core body temperature via non-shivering thermogenesis at room temperature.…”
Section: Discussionmentioning
confidence: 99%